Similar but not quite the same: Differential unique associations of trait fear and trait anxiety with inhibitory control - TOH, Wei Xing (Institutional Knowledge at Singapore Management University, 2020)
Given the dearth of research regarding the relations of trait fear and trait anxiety to cognitive control processes, we sought to investigate how trait fear and trait anxiety are uniquely related to inhibitory control, which is a crucial component of the regulatory processes that inhibit inappropriate responses that interfere with goal achievement. Given that inhibitory control tasks are often plagued by task-impurity issues, we employed a latent variable approach based on multiple measures of inhibitory control. We found that trait fear and trait anxiety are related but separable constructs that, when their shared variance was controlled for, predicted inhibitory control positively and negatively, respectively. Also, the unique negative relation between trait anxiety and inhibitory control was evident only for females. Our findings underscore distinct contributions of trait fear and trait anxiety to inhibitory control and the consideration of affective traits as multidimensional (e.g., valence and motivation) constructs to better understand the relation between negative affectivity and cognitive processes.